The Influence of Green Marketing, Brand Image, and Environmental Awareness on the Decision to Purchase Environmentally Friendly Products in Indonesia - Olayinka Funmi BABATUNDE; Sikiru Ayodeji ANIMASAUN (West Science Journal Economic and Entrepreneurship, 2026)
The increasing environmental problems faced by Indonesia have encouraged both consumers and businesses to pay greater attention to environmentally friendly products. This study aims to analyze the influence of green marketing, brand image, and environmental awareness on consumers’ decisions to purchase environmentally friendly products in Indonesia. A quantitative research approach was employed using a survey method involving 135 respondents who had experience or familiarity with green products. Data were collected through a structured questionnaire measured using a five-point Likert scale and analyzed using SPSS version 25. The analysis included validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results show that green marketing, brand image, and environmental awareness each have a positive and significant effect on purchase decisions, both individually and simultaneously. Among these variables, environmental awareness has the strongest influence on consumers’ purchasing decisions. These findings indicate that effective green marketing strategies, supported by a strong brand image and high consumer environmental awareness, play a crucial role in encouraging the purchase of environmentally friendly products. This study provides empirical evidence on green consumer behavior in Indonesia and offers practical implications for companies and policymakers in promoting sustainable consumption.